The impact of bilinguality and language context on the understanding of epistemic adverbs in health communication: the case of English and Russian - Nissen, Vanda; Meuter, Renata F. I. (Frontiers in Psychology, 2023)
Aim To explore how English epistemic adverbs, as used in health communication, are understood by speakers depending on their first language (L1) and language context. Methods We used an online dissimilarity rating task with paired doctors' opinions which differed only with respect to the embedded epistemic adverbs (e.g., This treatment definitely has side effects vs. This treatment possibly has side effects). In order to evaluate the possible effect of one's L1, we compared the ratings of English-speaking monolinguals and Russian-English bilinguals in Australia (Study 1). To evaluate the impact of language context, we compared the ratings of Russian-English bilinguals in Australia and Russia (Study 2). The data were interpreted using classical multidimensional scaling (C-MDS) analysis, complemented by cultural consensus analysis and hierarchical cluster analysis. Results The C-MDS analyses returned statistically acceptable results. Intragroup consensus was evident for all speaker groups. They all clustered the high confidence adverbs (clearly, definitely, and obviously) and the hearsay adverbs (presumably and supposedly) similarly. Effects of L1 were seen: for example, unlike the monolinguals, the Russian bilinguals did not include evidently with the high confidence adverbs (Study 1). An effect of context was also evident: Russian-English bilinguals in Australia most resembled the monolinguals in their understanding of epistemic adverbs. The way Russian-based bilinguals clustered epistemic adverbs reflected a less nuanced understanding (Study 2). Conclusion The subtle differences in how adverbs of likelihood and doubt are understood in health communication suggest extra care is needed when conveying risk and uncertainty to patients from diverse linguistic and/or cultural backgrounds to ensure mutual understanding and mitigate against miscommunication. The impact of L1 and language context on one's understanding highlights the need to explore more widely how epistemic adverbs are understood by diverse populations and, in doing so, improve healthcare communication practices.